The Waiting and Mating Game: Condition Dependent Mate Sampling in Female Gray Treefrogs (Hyla versicolor) - Bastien, Brandon; Farley, Gracie; Ge, Francis; Malin, Jacob S.; Simon-Plumb, Casey Lu; Pulley, Desta M.; Yang, Claire; Baugh, Alexander T. (Frontiers in Ecology and Evolution, 2018)
Strong sexual selection by receivers can lead to the evolution of elaborate courtship behaviors in signalers. However the process by which receivers sample signalers and execute mate choice under complex signaling conditions—and thus the realized strength of sexual selection—is poorly understood. Moreover, receivers can vary in condition, which can further influence mate sampling strategies. Using wild female frogs we tested two hypotheses at the intersection of these important problems: that some of the individual variation in mate sampling is explained by (1) the reproductive urgency hypothesis, which predicts that receivers in a more urgent reproductive state will sample mates less and/or (2) the reproductive investment hypothesis, which predicts that receivers that have invested less in the current reproductive effort will sample mates less. Eastern gray treefrogs, Hyla versicolor, were collected in amplexus and repeatedly tested for phonotaxis behavior using a dynamic playback assay. To evaluate if hormonal mechanisms explained variation in the mate sampling, three steroid hormones, estradiol, progesterone, and corticosterone, were collected using a noninvasive water-borne hormone assay, validated for this species in the present study. Finally, we measured clutch size (investment) and the duration of time required for each female to oviposit after being reunited with their male mate (urgency). We found repeatability in many of the behaviors, including mate sampling. We found that females with higher concentrations estradiol and corticosterone made quicker choices, and that females with higher progesterone sampled mates more. We also found that female frogs in a more urgent reproductive state had lower concentrations of progesterone and estradiol, thereby providing the first evidence of a relationship between gonadal hormones and reproductive urgency. Collectively we found some support for the reproductive urgency but not the investment hypothesis. Thus, even though a female frog’s reproductive readiness is a highly transient life history stage, fine scale variation in her reproductive timeline could mitigate the strength of directional selection.